INSIGHTS INTO TRANSFORMING THE UNIVERSITY FROM DIFFERENT REGIONS OF THE WORLD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
TOMSK, Russia, June 2015 – Representatives from various universities around the world converged at Tomsk State University (TSU) Russia to share insights on challenges faced in transforming their respective institutions in order to remain relevant in a rapidly changing world.